Selective C-F and Ni-C Bond Activation of Fluoronickelacycles as a Function of Ancillary Ligands - Giffin, Kaitlyn Anne (Université d'Ottawa / University of Ottawa, 2017)
The development of new unconventional routes to small functionalized fluorocarbons (FCs) continues to be an attractive target due to the high utility of FCs in a broad range of applications, including their use as refrigerants, solvents, and surfactants. With the phasing out of hydrofluoroalkanes as refrigerants, there is a growing interest in the synthesis of new hydrofluoroolefins (HFOs), which are known to have significantly reduced global warming potential relative to hydrofluoroalkanes. Currently, energy-intensive conditions and toxic starting materials are typically necessary for their syntheses, making these processes environmentally problematic. The approach we have proposed for alternative ‘greener’ methods for functionalized FC production targets a transition metal-catalyzed synthesis involving the formation of metallacyclic intermediates through the oxidative cycloaddition of simple fluorinated alkenes, e.g., tetrafluoroethylene (TFE) and trifluoroethylene (TrFE), at low-valent nickel centres. There is precedent for the generation of short fluoroalkyl chain (C4-C6) compounds through homogeneous catalysis. For example, Baker et al. showed that you could catalytically hydrodimerize two molecules of tetrafluoroethylene (TFE) or one molecule of TFE with one molecule of ethylene using low valent Ni catalysts and π-acidic monodentate ancillary ligands, affording octafluorobutane and 1,1,2,2-tetrafluorobutane respectively. The objective of this Thesis is to further the state-of-the-art in fluoroorganometallic chemistry by gaining a deeper understanding of transition metal fluoroalkyl complexes as a function of metal-fluoroalkyl and carbon-fluorine bond reactivity. The over-arching goal is to harness said reactivity for the synthesis of new value-added fluorocarbons. Due to the robust nature of carbon-fluorine and metal-fluoroalkyl bonds in transition metal fluoroalkyl complexes, intensive conditions are often necessary to achieve any reactivity. Recently, bifunctional ligands have proven to be useful at effecting challenging transformations through unconventional ligand-assisted substrate activation pathways. Chapters 2 and 3 herein explore the use of a bidentate phosphinothiol ligand in the context of perfluoronickelacyclopentane reactivity. Synthetic approaches for the formation of phosphinothioether- and phosphinothiolate-supported perfluorometallacycles are outlined along with ensuing reactivity studies, including examples of Cα-F, Cβ-F, and Ni-Cα bond activation. Furthermore, a metal-mediated synthesis of functionalized FC, (E)-1,2,3,3,4,4-hexafluoro-1-butene, is provided. Chapter 4 sheds light on the comparatively underdeveloped chemistry of fluorinated nickelacycles generated from TrFE. A systematic study of monodentate phophine and phosphite ligand effects on metallacyclopentane regio-/stereochemistry is presented. The behaviour of the generated hydrofluoronickelacyclopentanes in the presence of acidic additives allows for a direct analogy to be made regarding the effects of the extent of metallacycle fluorination on C-F and Ni-C activation. In search of new approaches to novel functionalized FC synthesis, Chapter 5 will re-visit the use of bifunctional ligands, investigating the formation and reactivity of new perfluoronickelacycles featuring [P,NH] and [P,Nˉ] bidentate ligands. Finally, Chapter 6 summarizes the findings of this Thesis and discusses some of the future opportunities that will build on this work. The increased understanding of the stoichiometric systems presented herein will be directly important to the development of nickel-catalyzed routes to HFOs. As the demand for new “greener” refrigerants and propellants increases, the synthesis of small-molecule functionalized FCs using transition metal catalysis and waste fluorinated feedstocks can offer a mild, atom economical approach to new, unique candidates that will be appealing to industrial partners.
Keywords: fluorine; organometallic chemistry; fluoroorganometallic chemistry; organofluorine compounds; nickel; transition metal chemistry